2015
DOI: 10.1530/jme-15-0075
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin induces adipose insulin resistance and autophagic imbalance via TNFR1 in mice

Abstract: Progranulin (PGRN) has recently emerged as an important regulator for insulin resistance. However, the direct effect of PGRN in vivo and the underlying role of progranulin in adipose insulin resistance involving the autophagy mechanism is not fully understood. In this study, mice treated with PGRN for 21 days exhibited the impaired glucose tolerance and insulin sensitivity, remarkable adipose autophagy as well as attenuated insulin signaling via inhibition of mammalian target of rapamycin (mTOR) pathway. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…In mice, progranulin treatment induces insulin resistance and adipose autophagy via mTOR (mammalian target of rapamycin) and TNFR1. 38 Our present data in a large cohort of humans with severe obesity support these findings and report a significant and positive correlation of progranulin serum concentrations with HbA1c levels, CRP levels and-on the basis of a trend-the occurrence of overt diabetes. According to the present data, the adipose tissue clearly is not the main source of circulating progranulin levels in obesity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In mice, progranulin treatment induces insulin resistance and adipose autophagy via mTOR (mammalian target of rapamycin) and TNFR1. 38 Our present data in a large cohort of humans with severe obesity support these findings and report a significant and positive correlation of progranulin serum concentrations with HbA1c levels, CRP levels and-on the basis of a trend-the occurrence of overt diabetes. According to the present data, the adipose tissue clearly is not the main source of circulating progranulin levels in obesity.…”
Section: Discussionsupporting
confidence: 86%
“…There is evidence that progranulin might represent a molecular mediator of adipose tissue and systemic insulin resistance. In mice, progranulin treatment induces insulin resistance and adipose autophagy via mTOR (mammalian target of rapamycin) and TNFR1 . Moreover, autophagy induced by oxidative stress and endoplasmatic reticulum stress seems to play a role in progranulin‐induced adipose tissue insulin resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have found that recombinant PGRN protein is therapeutic against Gaucher disease (Jian et al, 2016). However, there is concern for the long-term usage of PGRN as a drug due to potential oncogenic activity of this growth factor and the established elevation of PGRN levels in various cancer tissues relative to healthy counterparts (Bateman and Bennett, 2009, He and Bateman, 1999, He et al, 2002, Zhou et al, 2015). To address this issue, we devoted considerable effort toward developing a PGRN-derived molecule that retains the GCase-binding and therapeutic activity of PGRN but lacks its oncogenic action.…”
Section: Resultsmentioning
confidence: 99%
“…PGRN has been reported to show a therapeutic effect in vivo through its interaction with TNFRs in multiple murine models of inflammatory arthritis . Moreover, the PGRN/TNFR interaction has been confirmed and extended in multiple disease models …”
Section: Pgrn Modulates Tnf/tnfr Signalingmentioning
confidence: 87%
“…36,49 Moreover, the PGRN/TNFR interaction has been confirmed and extended in multiple disease models. 15,28,29,31,36,48,49,52,53,[56][57][58][59][60][61][62][63][64][65][66][67][68] More specifically, it has been reported that the PGRN-TNFR interaction plays an important role in the endoplasmic reticulum (ER) stress response. 60 Deletion of PGRN leads to increased susceptibility to ER stress-induced apoptosis; however, the administration of rPGRN successfully protects against ER stress-induced cell death.…”
Section: Pgrn Modulates Tnf/tnfr Signalingmentioning
confidence: 99%